ANALISIS HKSA SENYAWA TURUNAN EURIKUMANON SEBAGAI ANTIMALARIA MENGGUNAKAN PENDEKATAN REGRESI LINIER BERGANDA - Hanifah Yusuf; Mustofa; Mahardika Agus Wijayanti; Ratna Asmah Susidarti; Andrian Saputra; Iqmal Tahir (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Quantitative Structure Activity Relationship (HKSA) study of eurycomanone derivatives as antimalarial compound was done using multiple linear regression approaches. HKSA equation was obtained from theoretical descriptors data which involved atomic net charges (q), partition coefficient (log P), molecular volume (VM), molecular surface area (LP), molecular weight (BM), and HOMO-LUMO energy differences (EHOMO-ELUMO) versus minimum concentration to inhibit 50% of parasite growth Plasmodium falciparum (log IC50) growth. Descriptors data were obtained by applying AM1 semiempirical quantum mechanics calculation using Hyperchem 7.5 software, while the regression data processes were runned using SPSS 17.0 program. Based on multiple linear regression approaches, there is a selected quantitative relationship between log IC50 to the descriptors that was shown by HKSA equation below: Log IC50 = – 3048.930 + 5137.957qC2 – 13799.126qC5 – 1537.764qC12 + 556.313qC16 – 817.654qO29 + 4.654log P – 0.146VM + 0.270BM with n =10, r = 0.982, SE = 1.262, Fcalc/Ftable = 17.805, and PRESS = 1.593